Analysis of dyes using chromatography - Lewis, Simon (Woodhead Publishing Limited, 2009)
The colour of fibre, present naturally or imparted through use of a dye or pigment, can be extremely discriminating for the forensic scientist. One approach for colour analysis available to the forensic scientist is chromatography and, while partially destructive of the evidence, it can provide a much greater degree of discrimination than physical or optical methods alone. This chapter will give an overview of fibres focussing on thin-layer chromatography (TLC). Other approaches to instrumental chromatography analysis of dyes, including high performance liquid chromatography (HPLC) and capillary electrophoresis (CE) will be discussed.